(untitled) (Economics and region, 2025)
The higher the stability of the enterprise, the more independent it is from external factors of the market situation and, as a result, the lower the risk of bankruptcy. A large number of factors influence the sustainable development of the enterprise. Factors can differ in structure (simple and complex), in the significance of the result (primary and secondary secondary), in duration (permanent and temporary). However, all these factors can be divided into internal, depending on the reason for their occurrence, depending on the organization of the enterprise’s work, and external factors that are not subject to the will of the organization. The analysis pays special attention to internal factors, since the enterprise can to some extent control and influence them. The enterprise does not have the opportunity to influence external factors, it can only adapt its work to their changes as profitably as possible. Various methods for assessing the state of sustainable development of the enterprise, as a rule, repeat and complement each other, therefore, depending on the objectives of the analysis and the available database, they can be used both comprehensively and separately. Factor analysis is a method used to study the influence of a number of factors on the results, to determine the degree of influence of each of them. This method is indispensable for assessing the causes of changes in a given indicator. As an example, we can cite the method of chain substitution, as well as the equally general method of absolute and relative differences. The sustainable development of an enterprise is greatly influenced by factors that can be divided into external and internal. Internal ones directly depend on the organization of the work of the enterprise itself; changing external ones is almost not subject to the will of the enterprise. This division must be followed when modeling production and economic activities and trying to manage financial stability by carrying out a complex search for reserves to increase production efficiency. At the same time, an enterprise with good sustainable development has no problems with the state and society, since taxes and social contributions are paid on time, workers and employees receive their salaries on time, shareholders receive their dividends, and the enterprise guarantees the repayment of loans. In this regard, it is relevant to study the main aspects of the formation, use and management of working capital, and determine their role in the sustainable development of the enterprise.